Chardonnay grape seed flour supplemented diets alter intestinal microbiota in diet‐induced obese mice. Issue 5 (27th June 2017) - Seo, Kun‐Ho; Kim, Dong‐Hyeon; Jeong, Dana; Yokoyama, Wallace; Kim, Hyunsook
Abstract: The intestinal microbiota of mice was evaluated after supplementation with flavonoid‐rich whole grape seed flour from white winemaking. High‐fat (HF)‐diet‐induced obese (DIO) mice were fed a HF diet supplemented with either 10% partially defatted chardonnay grape seed flour (ChrSd) or microcrystalline cellulose (MCC, control) for 6 weeks. Supplementation with ChrSd reduced HF‐diet‐induced weight gain, liver and adipose tissue weight, and plasma lipid levels. The results from high‐throughput sequencing of the 16S rRNA V3‐4 region showed dynamic changes in the intestinal microbiome that are closely associated with the regulation of diet‐induced obesity, polyphenol conversion, bile acid and hepatic lipid metabolism, and butyrate production. Body and adipose tissue weight gain and plasma LDL concentration were positively associated with Lactobacillus and negatively associated with Roseburia and Enterococcus . In conclusion, chardonnay grape seed flour ameliorates the effects of a HF diet on plasma lipid concentration and adipose tissue and body weight, possibly via modulation of the intestinal microbiota in DIO mice. Practical applications: Construction of a healthy intestinal microbiota via prebiotic action using a flavonoid‐rich ChrSd diet may be an effective manner for the prevention of obesity and obesity‐related metabolic diseases.